Defining a differentiation strategy in the undifferentiated jewellery retail sector - Reis, Hugo Miguel Sismeiro (2015)
The ambition of realizing a project that might be useful in practical terms was the incentive to develop this project regarding the company that was born within my family – Ourivesaria Charme. Counting with twenty years of experience, this company develops its jewellery retailing activity in one of the main avenues of Leiria. Although having a solid position in the Jewellery Retail Sector, in Leiria, the lack of a clear strategic definition and a differentiating value proposition, in a market that is completely homogeneous in what concerns with the strategic planning, not only reveals real barriers to its own development, but also exposes the company to emerging threats from the constant changes of the external environment. Therefore, this project proposes to develop a differentiation strategy for Ourivesaria Charme. Even though developing its activity within a highly fragmented and competitive sector, which in turn has been affected by an unfavorable social and economic scenario, the strategy is oriented to the middle and middle-high social classes, and intends to increase the perceived benefit of the customers’ experience in Ourivesaria Charme. Thus, the value proposition is essentially based on the emotional side of the customers’ purchase experience, passing through the development of strong relationships based on loyalty with customers, providing them a customer service of excellence, combined with a portfolio that excels for its sophistication. Finally, the strategy takes shape through the innovation of several variables from the marketing and retailing mix, aiming to maximize customers’ satisfaction, through a sophistication of the most valued variables, guaranteeing a sustainable competitive advantage.